2012
DOI: 10.1097/spv.0b013e3182486e60
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Is Markedly Improved in Patients With Fecal Incontinence After Sacral Nerve Stimulation

Abstract: Sacral nerve stimulation not only restores or improves continence in treated patients with chronic FI but also improves their quality of life and symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 9 publications
3
29
0
Order By: Relevance
“…Previous publications from this study provide additional detail regarding study procedures. [10][11][12][13] the study protocol was approved by the fDa and institutional review boards at all participating institutions. the present article provides an overview of the 120 patients who received the sns therapy, but focuses on the long-term durability of the therapy in the patients who were followed for at least 5 years after device implantation at the time of data cutoff for this article (february 22, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Previous publications from this study provide additional detail regarding study procedures. [10][11][12][13] the study protocol was approved by the fDa and institutional review boards at all participating institutions. the present article provides an overview of the 120 patients who received the sns therapy, but focuses on the long-term durability of the therapy in the patients who were followed for at least 5 years after device implantation at the time of data cutoff for this article (february 22, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…At approximately 9 months of follow-up, no treatment failures occurred in the patients who underwent phase II implantation [30•]. A multicenter study with 4-year follow-up reported that 87 % of patients had a greater than 50 % reduction in FI episodes and a significant improvement in all QOL outcome measures [31].…”
Section: Snm For Other Pelvic Floor Disordersmentioning
confidence: 99%
“…Widespread adoption of many of these devices and resources has led to improved quality of life and survival in affected patient populations. [1][2][3][4][5][6][7][8][9] Heart disease remains the leading cause of death in the United States. 10 Despite progressive decline in deaths due to coronary artery disease and acute myocardial infarction attributed to the combination of public awareness, early treatment, and aggressive preventive strategies, a large percentage of health care spending is devoted to the management of patients with heart disease.…”
Section: Introductionmentioning
confidence: 99%